Local Wisdom dan Penetapan Hukum Islam di Indonesia - Sagaf Pettalongi (TSAQAFAH, 2012)
Local wisdom or in terms of fiqhi is called  al-urfis something that is a customs and traditions of a society in the form of words or deeds or things leave something .Local wisdom or tradition,which does not contradict the basic principles of the teaching of Islam may be regarded as confir med as the shari’a law. The priests madhahib many legal opinion based on the consideration of local wisdom (al-‘urf). In Indonesia there are three theories that are commonly used to keep the customary law and Islamic law ,namely:Receptio in complex theory ,Receptie theory and Receptio a contrario theory .Local wisdom has played an important role towards the establishment of Islamic law in both the establishment and enforcement of Islamic law .Some scholars deter mined requirements to make the local wisdom  (‘urf) as a source of Islamic law (1) local wisdom apply in the majority of cases occuring amongs the people and its implementation embraced by the majority community ,(2)  ‘urf existed before the emergence of cases which would set the law ,(3) local wisdom is not contrary to clearly expressed in a contract, (4) local wisdom does not conflict with nash.